Standardized Documentation of Oral Nutrition Supplements in the Electronic Medical Record - Smith, Rebecca E. (My University, 2019)
Malnutrition is a significant problem in hospitalized patients and a major cause for poor patient outcomes including: increased length of stay, readmission rates, hospital costs, and mortality. Methods to improve the documentation of oral nutrition supplements in the electronic medical record are needed to improve nutrition monitoring and patient care outcomes. The aim of this project is to increase nursing documentation compliance of oral nutrition supplements within the electronic medical records through implementing a standardized process. This quality improvement project was implemented over four months, on a 43-bed pulmonary/oncology unit, within an 800-bed acute care hospital. This process improvement was evaluated using pre- and post-implementation chart reviews and staff surveys. Staff education was initiated prior to implementation of the process change and resulted in a 131.8% increase in nursing documentation pre versus post-implementation. While limitations to the study were discovered, standardized documentation of oral nutrition supplements proved to be an effective strategy to improve documentation in hospitalized patients.
Keywords: Malnutrition; Readmission; Nutritional risk; Length of Stay; Outcomes